The combined influences of local heat application and resistance exercise on the acute mRNA response of skeletal muscle - McGlynn, Mark L.; Rosales, Alejandro M.; Collins, Christopher W.; Slivka, Dustin R. (Frontiers in Physiology, 2024)
Introduction The development and maintenance of the skeletal muscle is crucial for the support of daily function. Heat, when applied locally, has shown substantial promise in the maintenance of the muscle. The purpose of this study was to determine the combined effects of local heat application and acute resistance exercise on gene expression associated with the human muscle growth program. Materials and methods Participants (n = 12, 26 ± 7 years, 1.77 ± 0.07 m, 79.6 ± 15.4 kg, and 16.1 ± 11.6 %BF) completed an acute bilateral bout of resistance exercise consisting of leg press (11 ± 2 reps; 170 ± 37 kg) and leg extension (11 ± 1 reps; 58 ± 18 kg). Participants wore a thermal wrap containing circulating fluid (40°C, exercise + heat; EX + HT) during the entire experimental period and 4 h post-exercise, while the other leg served as an exercise-only (EX) control. Biopsies of the vastus lateralis were collected (Pre, Post, and 4hPost) for gene expression analyses. Results Intramuscular temperatures increased (Post, +2.2°C ± 0.7°C, and p < 0.001; 4hPost, +2.5°C ± 0.6°C, and p < 0.001) and were greater in the EX + HT leg post-exercise (+0.35°C ± 0.3°C, and p = 0.005) and after 4hPost (+2.1°C ± 0.8°C and p < 0.001). MYO-D1 mRNA was greater in the EX + HT leg vs. the EX (fold change = 2.74 ± 0.42 vs. 1.70 ± 0.28, p = 0.037). No other genes demonstrated temperature sensitivity when comparing both legs (p > 0.05). mRNA associated with the negative regulator, myostatin (MSTN), decreased post-exercise (p = 0.001) and after 4 h (p = 0.001). mRNA associated with proteolysis decreased post-exercise (FBXO32, p = 0.001; FOXO3a, p = 0.001) and after 4 h (FBXO32, p = 0.001; FOXO3a, p = 0.027). Conclusion The elevated transcription of the myogenic differentiation factor 1 (MYO-D1) after exercise in the heated condition may provide a mechanism by which muscle growth could be enhanced.